ANTIBACTERIAL ACTIVITY OF HYDROXYAPATITE FROM FRESHWATER MUSSEL SHELL (Pilsbryochoncha sp.) AGAINST Streptococcus mutants BACTERIA - Sidauruk, Santhy Wisuda; Rusdi, Rizky Ramadhan; Sari, N. Ira (Politeknik Kelautan dan Perikanan Dumai, 2024)
Unutilized mussel shells have the potential to become solid waste and potentially pollute the environment. In fact, the shell has a high calcium content of 61.39% which can be used as a precursor to hydroxyapatite. Hydroxyapatite is known to have antibacterial activity that causes dental caries, namely Streptococcus mutants. However, the antibacterial activity of HAp from mussel shells against S. mutans bacteria is not yet known. This study aims to determine the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and determine the inhibition zone against S. mutants bacteria from hydroxyapatite of mussel shells. This research procedure started from hydroxyapatite synthesis, MIC test, MBC test, and inhibition zone analysis at several HAp concentrations, namely 12.5 mg/mL, 25 mg/mL, and 50 mg/mL, as well as positive control and negative control. The results showed that no KHM and KBM values were found at the HAp concentrations used. Furthermore, the diameter of the hydroxyapatite inhibition zone against S. mutants bacteria at concentrations of 12.5 mg/mL, 25 mg/mL, and 50 mg/mL, was 0 mm. Thus, the hydroxyapatite of mussel shells is neither bacteriostatic nor bacteriocidal.